Islamic Education: Pillars of Tolerance and Harmony in Multicultural Societies - Zulfikah Nur; Syahruddin Usman; Saprin (Kasyafa: Jurnal Pendidikan Agama Islam, 2025)
Islamic education has a strategic role in realizing tolerance and harmony in a multicultural society characterized by diversity of ethnicities, religions, cultures, and languages. This article aims to analyze the contribution of Islamic education in building an attitude of mutual respect and strengthening shared values ​​through a multicultural approach. Using a literature review method, this article explores academic perspectives on Islamic education and its relevance in the context of cultural diversity. The results of the study indicate that Islamic education can integrate multicultural values ​​through the curriculum, strengthening educator competence, and implementing cross-cultural dialogue. In addition, multicultural-based Islamic education can reduce negative prejudice, foster respect for differences, and build a peaceful and inclusive society. Thus, Islamic education is not only a means of transferring knowledge but also a medium for forming students' characters who respect plurality in community life.